The Influence of Tax Service Quality and Tax Rate on Taxpayer Compliance among SMEs in Indonesia - Hadiwibowo, Imam; Jufri, Ali; Lusiyana, Desy (Universitas Muhammadiyah Semarang, 2023)
SMEs are a form of community business to support the country's economy during the covid-19 pandemic, SMEs are the most affected businesses. This study aims to determine the level of compliance of SMEs taxpayers in terms of tax rates, quality of fiscal service, and taxpayer self assessment system. The population in this study were SMEs registered at KPP Pratama Cirebon 2. The data analysis method used is descriptive statistics using structural equation model (SEM) analysis. The research results show that there is an effect of tax rate on the self assessment system, quality of tax service on the self assessment system, there is a relationship between tax rate and quality of tax service, there is no effect of the self assessment system on taxpayer compliance, there is no effect of tax rate on taxpayer compliance, there is no influence of fiscal service quality on taxpayer compliance. The hope is that tax rate and fiscal services become important factors in increasing taxpayer compliance